Afselvfølgeliggørelse - Idéhistoriens raison d’etre - Lassen, Frank Beck (Slagmark - Tidsskrift for idéhistorie, 2018)
In his Essays the philosopher and writer Michel de Montaigne argued, that “no propositions astonish me, no belief offends me, though never so contrary to my own; there is no so frivolous and extravagant fancy that does not seem to me suitable to the production of human wit. We, who deprive our judgment of the right of determining, look indifferently upon the diverse opinions, and if we incline not our judgment to them, yet we easily give them the hearing. In the present article I am going to argue that the three protagonists of this dissertation have made a number of observations similar to that of Montaignes, albeit from different perspectives, regarding the uses of history. These observations I shall try to connect through the notion of ‘denaturalisation’ (afselvfølgeliggørelse). The value of history can be said to be about the alien character of history, and about all of the ways in which we no longer view our societies. By studying past beliefs and convictions, we might be able to distance ourselves from the assumptions about our own time that we take for granted.